PERAN KEGIATAN LITERASI TERHADAP PEMBENTUKAN KARAKTER MAHASISWA PENDIDIKAN AGAMA ISLAM FTK-UNIKS - Ikrima Mailani; Zulhaini Zulhaini; Fernanda Effendi (Journal of Research and Thought on Islamic Education (JRTIE), 2020)
Abstract: In this XXI century humans have been flooded with information as a result of the increasingly rapid development of information communication technology using digital media as a tool. In order to avoid paradox, digital media literacy skills are needed, so that digital media users are ready to face this era of information flood. On the other hand, education has undergone a reform in which character education has become an important part of forming complete human resources so that strengthening character building has even been integrated in learning activities along with literacy activities. In the Islamic Education’s Department at FTK-UNIKS, digital media literacy-based learning activities have been implemented, but have not emphasized the dimensions of student character. Based on the explanation above, this research can be formulated as follows: What is the role of digital media literacy activities in shaping the character of students of the PAI FTK-UNIKS study program? This research is a qualitative descriptive study conducted at the campus of the Islamic Education’s Department at FTK-UNIKS. Data collection uses the method of observation and documentation and is analyzed using qualitative analysis. The result of the research is that literacy activities play a very important role in shaping the character of students of the PAI FTK-UNIKS study program, namely the sub-values of religious, nationalist, independent, mutual cooperation, integration. Keywords: Literacy Activities, Character Building